Characterization of Parkinson's disease-related pathogenic TMEM230 mutants - Nam, Daleum; Kim, Hyejung; Choi, Dong-Joo; Bae, Yun-Hee; Lee, Byoung Dae; Son, Ilhong; Seol, Wongi (Animal cells and systems, 2018)
Parkinson's disease (PD) is the second most common neurodegenerative disease. Although most PD cases are sporadic, 5-10% of them are hereditary and several pathogenic mutations in related genes have been identified. Mutations in TMEM230 were recently identified as a cause of autosomal dominant PD. However, the basic properties of the mutant proteins are not yet known. We examined stability and neurotoxicity, important characteristics of PD pathogenesis-related proteins, of WT TMEM230 and two pathogenic mutants, R78L and PG5ext, in a dopaminergic neuronal cell line. Our study showed that amount of protein expressed in the same vector backbone was R78L > WT > PG5ext. The stabilities of the mutant proteins were similar to each other, but lower than that of the WT. In addition, overexpression of mutants and WT TMEM230 caused similar levels of neurotoxicity upon MPP + treatment when compared to the cells transfected with an empty vector. Because the proteins encoded by two PD-causing genes, TMEM230 and LRRK2, function in vesicle trafficking, we tested whether they interact. LRRK2 neither interacts with, nor phosphorylates TMEM230. We also investigated the levels of several Rab proteins (Rab1A, 5, 7, 8A and 11) involved in vesicle trafficking after TMEM230 overexpression. However, there was no clear difference of any Rab proteins among cells transfected with an empty vector, TMEM230 WT and mutants-expressing cells, suggesting that TMEM230 does not directly regulate these Rab proteins. Thus, these TMEM230 PG5ext and R78L mutant proteins are not distinctly different from the WT proteins except for their stability. Abbreviations: LRRK2: Leucine-rich repeat kinase 2; PD: Parkinson's disease; AD: Alzheimer's disease; RT-PCR: reverse transcription-polymerase chain reaction; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; FACS: fluorescence-activated cell sorting; PBS: phosphate buffered saline; FBS: fetal bovine serum; PI: propidium iodide.